Exercise-Induced Benefits for Alzheimer’s Disease by Stimulating Mitophagy and Improving Mitochondrial Function - Liang, Jiling; Wang, Cenyi; Zhang, Hu; Huang, Jielun; Xie, Juying; Chen, Ning (Frontiers in Aging Neuroscience, 2021)
Neurons are highly specialized post-mitotic cells that are inherently dependent on mitochondria due to their higher bioenergetic demand. Mitochondrial dysfunction is closely associated with a variety of aging-related neurological disorders, such as Alzheimer's disease (AD), and the accumulation of dysfunctional and superfluous mitochondria has been reported as an early stage that significantly facilitates the progression of AD. Mitochondrial damage causes bioenergetic deficiency, intracellular calcium imbalance and oxidative stress, thereby aggravating β-amyloid (Aβ) accumulation and Tau hyperphosphorylation, and further leading to cognitive decline and memory loss. Although there is an intricate parallel relationship between mitochondrial dysfunction and AD, their triggering factors, such as Aβ aggregation and hyperphosphorylated Tau protein and action time, are still unclear. Moreover, many studies have confirmed abnormal mitochondrial biosynthesis, dynamics and functions will present once the mitochondrial quality control is impaired, thus leading to aggravated AD pathological changes. Accumulating evidence shows beneficial effects of appropriate exercise on improved mitophagy and mitochondrial function to promote mitochondrial plasticity, reduce oxidative stress, enhance cognitive capacity and reduce the risks of cognitive impairment and dementia in later life. Therefore, stimulating mitophagy and optimizing mitochondrial function through exercise may forestall the neurodegenerative process of AD.